VEGF-D Serum Level as a Potential Predictor of Lymph Node Metastasis and Prognosis in Vulvar Squamous Cell Carcinoma Patients - Ravaggi, Antonella; Gambino, Angela; Ferrari, Federico; Olivari, Alessandro; Zanotti, Laura; Romani, Chiara; Ardighieri, Laura; Antonelli, Paolo; Garganese, Giorgia; Gallo, Daniela; Scambia, Giovanni; Bignotti, Eliana; et al. (Frontiers in Oncology, 2022)
Background: Radical surgical resection of the primary tumor with mono/bilateral inguinofemoral lymph node dissection is the standard treatment for invasive vulvar squamous cell carcinoma (VSCC) and is frequently related to severe morbidity. Tailoring surgical treatment is of paramount importance and a comprehensive preoperative evaluation is mandatory. Vascular endothelial growth factor-D (VEGF-D) is considered a regulator of lymphangiogenesis, involved in tumor spread via lymphatic vessels. The aim of this study is to evaluate the potential of VEGF-D in the prediction of inguinofemoral lymph node metastasis. Methods: We analyzed preoperative VEGF-D serum (sVEGF-D) levels from two independent cohorts of VSCC patients by enzyme-linked immunoadsorbent assay and its protein expression on tumor tissue by immunohistochemistry. Logistic regression was performed to identify independent risk factors for lymph node metastasis and Cox proportional hazard model was used for survival analysis. Results: High levels of sVEGF-D, but not tissue VEGF-D, significantly correlated with positive groin nodes and a more advanced FIGO stage. In multivariable analysis, a high sVEGF-D level was an independent predictor of lymph node metastasis and worse prognosis. A prediction model based on sVEGF-D, tumor grade assessed on biopsy, tumor diameter, and lymph node clinical evaluation was able to predict lymph node metastasis, reaching a C-index of 0.79 and 0.73 in the training and validation cohort, respectively. Conclusions: Preoperative sVEGF-D level might be a reliable biomarker for prediction of lymph node metastasis and prognosis in VSCC patients, supporting a better clinical/surgical decision. Multicenter prospective studies are required to confirm our findings.